(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Technological advancements have led to a rise in automation, which has the potential to displace workers and increase unemployment. This paper examines the impact of automation on unemployment, considering both the short-term and long-term effects. It analyzes the potential for job creation in new sectors as a result of automation and discusses policy measures that can be implemented to mitigate the negative effects of job displacement.